Determinants Of Regional Economic Growth In Java Island: An Analysis Of Capital Expenditure, General Allocation Funds, And Labor Using A Fixed Effect Model (2020–2024) - Muhammad Daffarezel Ramadhan; Rifat Ahmad; Wildan Maulana Assani Mualim; Markus Kayame; Arina Romarina (CV. Ulil Albab Corp, 2026)
This study examines the impact of regional capital expenditure, General Allocation Funds (DAU), and labor on real per capita Gross Regional Domestic Product (GRDP) growth across 118 regencies and cities in Java Island from 2020 to 2024. Using a Fixed Effect Model (FEM) with clustered robust standard errors, the balanced panel dataset includes 590 observations from six provinces: Banten, DKI Jakarta, West Java, Central Java, Yogyakarta Special Region, and East Java. The findings show that capital expenditure per capita has a significant positive elasticity of 0.247 (p < 0.001), increasing to a cumulative 0.297 when including a one-year lag, indicating sustained effects of public investment. DAU per capita exhibits a positive but statistically insignificant elasticity of 0.089 (p = 0.145), suggesting potential flypaper effects or indirect influence through capital spending. Labor emerges as the strongest driver of growth, with an elasticity of 0.654 (p < 0.001), which is 2.65 times larger than the impact of capital expenditure. Diagnostic tests validate the model, showing corrected heteroskedasticity, marginal autocorrelation, low multicollinearity (maximum VIF = 3.45), and approximately normal residuals. The results highlight that while public infrastructure investment remains important, a skilled and productive labor force is the most critical determinant of regional growth. Policy recommendations include increasing central government allocations for productive infrastructure, enhancing local government human capital development and capital spending quality, and adopting multi-year evaluation frameworks to capture long-term infrastructure benefits. Future research should explore DAU mediation pathways and spatial spillover effects across jurisdictions.